The flower of May - O'Brien, Kate, 1897-1974. (London : Reading Book Club, 1955)
The Flower of May is bestselling Irish author Kate O$1 (BBrien$1 (Bs portrait of a young Irishwoman on the verge of independence set at the turn of the century. Liberated by the death of her mother, Fanny Morrow immerses herself in the politics and culture of Europe, renouncing her strict, Catholic upbringing.s
Keywords: Historical Fiction -- Fiction -- Ireland